Using a Combination of Intralaminar and Pedicular Screw Constructs for Enhancement of Spinal Stability and Maintenance of Correction in Patients With Sagittal Imbalance: Clinical Applications and Finite Element Analysis. Issue 8 (October 2016) - Inanmaz, Mustafa E.; Kose, Kamil C.; Atmaca, Halil; Ozkan, Arif; Isik, Cengiz; Basar, Hakan
Abstract : Study Design: Case series and finite element analysis. Objective: To report the clinical results of using intralaminar screw-rod (ILS) constructs as supplements to regular pedicle screw (PS) constructs in "high risk for implant failure" patients and to report the results of a finite element analysis (FEA) of this new instrumentation technique. Summary of Background Data: Despite advances in surgery and implantation techniques, osteoporosis, obesity, revision surgeries, and neuromuscular conditions (such as the Parkinson disease) are challenges against achieving solid arthrodesis and maintaining correction. Additional fixation strategies must be considered in these patients. There is only one study in the literature suggesting that ILS can be used as alternative anchor points and/or to increase fixation strength in conjunction with the PSs. Materials and Methods: Five patients (3 male and 2 female) with mechanical comorbidities underwent PS+ILS to treat sagittal imbalance. In radiologic analysis, thoracic kyphosis, lumbar lordosis, and sagittal vertical axis were analyzed. FEA of ILS augmentation technique were carried out. Four different models were created: (1) the full-construct model with ILS+PS 2 levels above and below the osteotomy of T10; (2) only PS 2 levels above and below T10; (3) ILS+PS 1 level above and below the osteotomy; and (4) short-segment PS with only PSs 1 level above and below the osteotomy. The stress/load distributions on the implants in vertebrae were analyzed. Results: The mean age of the patients included in this study was 41 years and the mean follow-up was 28.2 months. A total of 87 PSs and 39 ILSs were used. Both sagittal vertical axis and kyphosis angles showed significant improvements maintained at the latest follow-up. No pseudarthrosis or instrumentation failures were observed. FEA indicated that addition of ILS construct to a PS construct enabled decreased load bearing and increased implant life. Conclusions: Addition of an ILS construct to PS construct decreases osteotomy line deformation and reduces stress on pedicle fixation points, and the combination improves fixation stability over the conventional PS-rod technique.